2021
DOI: 10.3389/fcell.2021.614988
|View full text |Cite
|
Sign up to set email alerts
|

Human Wharton’s Jelly Stem Cell Secretions Inhibit Human Leukemic Cell Line K562 in vitro by Inducing Cell Cycle Arrest and Apoptosis

Abstract: Emerging resistance to the tyrosine kinase inhibitors that target the BCR-ABL1 oncoprotein has prompted research for novel therapeutics against chronic myeloid leukemia (CML). Herein, we evaluated the tumor inhibitory properties of the human Wharton’s jelly stem cells (hWJSCs) co-culture (hWJSC-CC) and their extracts, namely, the hWJSC-conditioned medium (hWJSC-CM; 100%) and hWJSC-lysate (hWJSC-L; 15 μg/ml), on a CML cell line K562 in vitro. The hWJSCs expressed mesenchymal stem cell (MSC)-related cluster of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Especially under febrile temperature conditions, T‐MSC‐CMs caused a significant decrease in the cells in the S phase fraction. These results obtained with K562 cells are similar to the findings on the study carried out by Huwaikem et al 68 Besides, in the study by Fathi et al, 69 it was reported that coculture of bone marrow derived MSCs with K562 cells caused cell cycle arrest in the G0/G1 phase. However, T‐MSC‐CMs prepared under different conditions in MOLT‐4 cells caused the arrest in the different cell fractions in these cells.…”
Section: Discussionsupporting
confidence: 90%
“…Especially under febrile temperature conditions, T‐MSC‐CMs caused a significant decrease in the cells in the S phase fraction. These results obtained with K562 cells are similar to the findings on the study carried out by Huwaikem et al 68 Besides, in the study by Fathi et al, 69 it was reported that coculture of bone marrow derived MSCs with K562 cells caused cell cycle arrest in the G0/G1 phase. However, T‐MSC‐CMs prepared under different conditions in MOLT‐4 cells caused the arrest in the different cell fractions in these cells.…”
Section: Discussionsupporting
confidence: 90%
“…It is reported similar promotive effect on apoptosiscell and cycle arrest in human leukemic cell line K562 treated with hUCMSCs and their extracts [50]. Besides, hUCMSC extracts are reported to inhibit ovarian cancer cell lines OVCAR3 and SKOV3 in vitro by inducing cell cycle arrest and apoptosis [11].…”
Section: Disccusionmentioning
confidence: 86%
“…Disregulation of the cell cycle is a sign of the progress of cancer cells, so preventing the progress of the cell cycle or inducing apoptosis is considered to be an important strategy for cancer treatment [ 30 ]. As we all know, cancer cells overcome the surveillance of the host and continue to survive by inhibiting cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%